Antibacterial Activity Test of Trump Extract Dendrophtoe petandra (L.) Miq. Against Pseudomonas aeruginosa in Vitro - Savitri, Lisa; Alves, Silvina Sandra X.; Hilmi, Mochammad Hanif; Krissanjaya, Rochmad; Prasetyawan, Fendy; Juwita, Syntia Tanu (Biology, Medicine, & Natural Product Chemistry, 2025)
Mistletoe (Dendrophthoe pentandra (L.) Miq.) is one of the plants found in Indonesia. The type of mistletoe commonly found is D. pentandra (L.) Miq. Apart from its parasitic nature, the leaves of D. pentandra (L.) Miq. has useful benefits as an antibacterial. Bacteria are divided into two groups based on their staining, namely Gram-positive bacteria and Gram-negative bacteria. Infectious diseases can be caused by several types of microorganisms in the bacterial group, including Pseudomonas aeruginosa. This study aims to determine the P. aeruginosa bacteria in the extract of lime mistletoe. This study used an experimental post-test only control research design with the disc diffusion method. This study used five concentrations, namely 20%, 40%, 60%, 80%, and 100%, and used distilled water as a negative control and ciprofloxacin as a positive control. The inhibition zone is determined by observing the clear zone.